Factors Affecting Farmers Income Generation from Ginger Production in Abia and Imo States, Nigeria - M., Mazza; E., Ewuziem J.; C., Uwandu, Q. (Canadian Journal of Agriculture and Crops, 2019)
The paper examined the factors that affect income generation from ginger farmers in Abia and Imo States, Nigeria. Multi-stage sampling technique was used to select 80 ginger farmers for the study. Data were obtained with the aid of structured interview schedule and Focus Group Discussion. The data collected were analyzed with descriptive statistics and regression. Result revealed that, majority of the ginger farmers in the study area were males and have average age of 53 years and average household size of 9 persons. They are all subsistence farmers, with average ginger farm size of 0.3 hectare. On average, the farmers are literate and with annual income of ₦72,487.5 from ginger production. The regression result shows that four variables namely age, farm size, educational level and income from other farm produce, were significant factors affecting farmers’ income generation. Farm size and income from other farm produce were positive and significant at 1%, while age and educational level were positive and significant at 5%. The study revealed that farmers rely on income from farm produces to increase their productivity. It was recommended that Government should ensure that farmers have access to credits so as to help them increase their productivity.